Rapid quantification of myocardial lipid content in humans using single breath-hold 1H MRS at 3 Tesla. - Rial, B; Robson, M; Neubauer, S; Schneider, J (2011)
A rapid, proton magnetic resonance spectroscopy method to evaluate human myocardial lipid levels in a single breath-hold at 3 T using a commercial whole-body system is presented. During a 10 s breath-hold, water unsuppressed and suppressed spectra were acquired by two phased array coils using a short-echo time spectroscopic stimulated echo (STEAM) sequence electrocardiogram-triggered to mid-diastole. Lipid-to-water ratios were obtained in the septum of 15 healthy volunteers, (0.46 ± 0.19)%. These results agreed well with ratios obtained from averaged spectra acquired in seven multiple breath-holds, (0.45 ± 0.20)%, providing increased signal-to-noise ratio but requiring longer acquisition times. Excellent correlation was found between the two methods (r=0.94, P<0.05). Reproducibility of (1)H MRS for measuring myocardial lipid levels in a short breath-hold was acceptable in five repeated measurements within the same subject (coefficient of variation=19%). Thus, single breath-hold proton spectroscopy allows reliable and quick quantification of myocardial lipids at 3 T.